Islam Reformed in Indian History: The Dynamic Sufi Heart in Vital Transition to Printed Scripture - Harlan O. Pearson (Teosofi: Jurnal Tasawuf dan Pemikiran Islam, 2021)
Attempting to comprehend the controversial subject of Islamic reform, this study compares the development of Indian Islam to the Protestant Reformation. Seminal findings from social science aid in understanding religious reform as an evolving historical process. During the transition to colonial rule in India, Christian missionaries introduced a scripturally defined concept of religion that challenged the traditional worldview with Sufis at the heart of organic universal order. Shah Waliullah interpreted the social disorder as the historical operation of the transcendent and willful God, declaring Islamic scriptures as the only authoritative guide for believers. Reformers translated the Qur’ān, preached to the masses, and established independent Muslim schools. Scripturalism expressed as literalism became puritanical resulting in sectarian fragmentation and conflict with Islamic and Christian reform. But the most disruptive change agent was technological: the printing press transformed scripture from oral and manuscript traditions, and the pervasive printed Qur’ān in local languages shaped individual and communal Muslim identity. The profound historical impact of religious reform with printed scripture could portend a new era with digital scripture in cyberspace.